Nerve high-resolution ultrasonography in peripheral nerve injuries associated with supracondylar humeral fractures in children. (January 2020) - Leonardi, Luca; Loreti, Simona; Di Pasquale, Antonella; Morino, Stefania; Fionda, Laura; Vanoli, Fiammetta; Garibaldi, Matteo; Antonini, Giovanni
Highlights: Peripheral nerve injuries can complicate upper limb fractures in children. EMG/NCS has several limitations in traumatic nerve injuries. EMG/NCS is often not tolerated in children. Nerve ultrasonography provides useful information in traumatic nerve injuries. Nerve ultrasonography is well tolerated in children. Abstract: To evaluate nerve high-resolution ultrasonography (HRUS) as diagnostic tool in children with supracondylar humeral fractures (SHF)-related peripheral nerve injuries (PNIs), we selected at least one illustrative case for each upper limb nerve usually involved in SHF (i.e. median, radial and ulnar nerve), in which HRUS evaluation added a useful contribution in diagnostic and therapeutic choices. We selected four patients (3 males, 1 female, aged between 7 and 12 years). Involved nerves were median (2), radial (1) and ulnar (1). HRUS results can actively modify the management of children with SHF-related PNIs, especially when combined with clinical and EDX. HRUS should be used routinely in evaluation of children with SHF-related PNIs.